China-Africa Health Development Initiatives: Benefits and Implications for Shaping Innovative and Evidence-informed National Health Policies and Programs in Sub-saharan African Countries - Ernest Tambo, PhD; Chidiebere E Ugwu, PhD; Yayi Guan, PhD; Ding Wei, MSc; Xiao Ning, PhD; Zhou Xiao-Nong, PhD (Global Health and Education Projects, Inc., 2016)
Background and Introduction: This review paper examines the growing implications of China's engagement in shaping innovative national initiatives against infectious diseases and poverty control and elimination in African countries. It seeks to understand the factors and enhancers that can promote mutual and innovative health development initiatives, and those that are necessary in generating reliable and quality data for evidence-based contextual policy, priorities and programs. Methods: We examined the China-Africa health cooperation in supporting global health agenda on infectious diseases such as malaria, schistosomiasis, Ebola, TB, HIV/AIDS, neglected tropical diseases (NTDs) prevention, control and elimination spanning a period of 10 years. We reviewed referenced publications, global support data, and extensive sources related to and other emerging epidemics and infectious diseases of poverty, programs and interventions, health systems development issues, challenges, opportunities and investments. Published literature in PubMed, Scopus, Google Scholar, Books and web-based peer-reviewed journal articles, government annual reports were assessed from the fi rst Forum on China-Africa Cooperation (FOCAC) in November 2006 to December 2015 Third Ministerial conferences. Results: Our findings highlight current shared public health challenges and emphasize the need to nurture, develop and establish effective, functional and sustainable health systems capacity to detect and respond to all public health threats and epidemic burdens, evidence-based programs and quality care outcomes. China's significant health diplomacy emphasizes the importance of health financing in establishing health development commitment and investment in improving the gains and opportunities, importantly efficiency and value health priorities and planning. Conclusions and Global Health Implications: Strengthening China-Africa health development agenda towards collective commitment and investment in quality care delivery, effective programs coverage and effi ciency, preparedness and emergency response is needed in transforming African health information systems, and local health governance structures and management in emerging epidemics. Furthermore, innovative evidence of operational joint solutions and strategies are critical in advancing healthcare delivery, and further enhancing Universal Health Care, and Sustainable Development Goals to attain global health improvements and economic prosperity. Key words: China-Africa • Partnership • Multilateralism • Engagement • National • Global Health  • Disease • Sustainable • Development Copyright © 2016 Tambo et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.